Graphene/iridium(III) dimer complex composite modified glassy carbon electrode as selective electrochemical sensor for determination of hydroquinone in real-life water samples. Issue 11 (2nd September 2022) - Mohd Yazid, Siti Nur Akmar; Md Isa, Illyas; Ali, Noorshida Mohd; Hashim, Norhayati; Saidin, Mohamad Idris; Ahmad, Mohamad Syahrizal; Asiri, Abdullah M.; Khan, Anish; Zainul, Rahadian
ABSTRACT: A novel electrochemical sensor for sensitive and selective detection of hydroquinone (HQ) was developed using graphene/iridium(III) dimer complex composite modified glassy carbon electrode (graphene/Ir(III) complex/GCE). The composite was characterised by field emission scanning electron microscopy, energy dispersive X-ray microanalysis, Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. The graphene/Ir(III) complex/GCE has provided higher surface area which was good for catalytic activity and enhanced electrical conductivity that was then examined using differential pulse voltammetry, cyclic voltammetry, and square wave voltammetry. At optimal condition, HQ has been sensitively detected in the ranges of 100–1.5 µM and 1.5–0.05 µM with good sensitivity of 1120.64 μA/mM/cm 2 and low detection limit of 1.1 nM ( S/N  = 3). The graphene/Ir(III) complex/GCE sensor presented the performance advantages of good reproducibility, repeatability, stability and selectivity. The prepared electrode was further applied to detect HQ in real-life water samples, which exhibit the acceptable recovery.